Racial Disparities and Outcomes After Left Ventricular Assist Device Implantation as Bridge to Transplantation or Destination Therapy. Issue 3 (May 2019) - Okoh, Alexis K.; Chan, Olivia; Schultheis, Molly; Fugar, Setri; Kang, Nathan; Kaplon, Sari; Karanam, Ravindra; Russo, Mark; Zucker, Mark; Camacho, Margarita
Abstract : Objective: We sought to investigate outcomes after left ventricular assist device (LVAD) implantation in advanced heart failure patients stratified by race. Methods: Patients who had LVADs inserted at a single center as a bridge to transplant (BTT) or destination therapy (DT) were divided into 3 groups based on race: Caucasian, African American (AA), and Hispanic. Postoperative outcomes including complications, discharge disposition, and survival at defined time points were compared. Cox proportional hazards were used to identify factors associated with 1-year all-cause survival. Results: A total of 158 patients who had LVADs as BTT ( n = 63) and DT ( n = 95) were studied. Of these, 56% ( n = 89) were Caucasians, 35% ( n = 55) were AA, and 9% ( n = 14) were Hispanics. AA patients had higher BMI and lower socioeconomic status and educational level, and were more likely to be single or divorced. Operative outcomes were similar among all 3 groups. Unadjusted 30-day, 6-month, 1-year, and 2-year survival rates for Caucasians versus AA versus Hispanics were 82% versus 89% versus 93%, P = 0.339; 74% versus 80% versus 71%, P = 0.596; 67% versus 76% versus 71%, P = 0.511; and 56% versus 62% versus 68%, P = 0.797. On multivariate analysis, device-related infection, malfunction, and abnormal rhythm were factors associated with overall all-cause mortality. Conclusion: AA patients who undergo LVAD implantation as BTT or DT have lower socioeconomic status and educational level compared to their Caucasian or Hispanic counterparts. These differences, however, do not translate into postimplant survival outcomes.